A New Species of Proceratophrys (Anura: Cycloramphidae) from Midwestern Brazil - Avila, Robson W.; Pansonato, Andre; Struessmann, Christine (Soc Study Amphibians Reptiles, 2012)
We describe adult morphology, advertisement call, and natural history aspects of a new frog species from riparian habitats alongside intermittent headwater streams in southwestern Cerrado, the second largest biome in Brazil. Presently known from three localities in Mato Grosso State, the new species belongs to the Proceratophrys cristiceps group. It is characterized mainly by small size (adult snout vent length approximately 46 mm), snout rounded in dorsal view and obtuse in lateral view, absence of flared lips, dorsal skin granular, and absence of both postocular swellings and prominent palpebral appendages. The advertisement call of the new species consists of a single note with 19-25 pulses. Calls are repeated at mean intervals of 0.7 sec. Mean dominant frequency is 1,250.2 Hz, with ascendant modulation.